To add the two fractions \( \frac{1}{2} (x + 4) \) and \( \frac{1}{4} (4x - 2) \), we first simplify each term.
-
Start with the first term: \[ \frac{1}{2} (x + 4) = \frac{1}{2}x + \frac{1}{2} \cdot 4 = \frac{1}{2}x + 2 \]
-
Now, simplify the second term: \[ \frac{1}{4} (4x - 2) = \frac{1}{4} \cdot 4x - \frac{1}{4} \cdot 2 = x - \frac{1}{2} \]
Now we can combine the two terms: \[ \left( \frac{1}{2}x + 2 \right) + \left( x - \frac{1}{2} \right) \]
Combine like terms:
-
The \( x \) terms: \[ \frac{1}{2}x + x = \frac{1}{2}x + \frac{2}{2}x = \frac{3}{2}x \]
-
The constant terms: \[ 2 - \frac{1}{2} = 2 - 0.5 = \frac{4}{2} - \frac{1}{2} = \frac{3}{2} \]
Putting it all together, we have: \[ \frac{3}{2}x + \frac{3}{2} \]
To express this in mixed form, we can factor out \( \frac{3}{2} \): \[ \frac{3}{2}(x + 1) \]
Thus, the sum \( \frac{1}{2} (x + 4) + \frac{1}{4} (4x - 2) \) in mixed form is: \[ \frac{3}{2}(x + 1) \]